PENGARUH MODEL COURSE REVIEW HORAY BERBANTUAN PLATFORM WORDWALL TERHADAP KEMAMPUAN BERPIKIR KRITIS PENDIDIKAN PANCASILA SISWA KELAS IV SD GUGUS VI KECAMATAN SUKASADA - Kadek Sima Yuni; I Made Suweta; Ni Putu Candra Prastya Dewi (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
The problem that occurred in the research location was based on the low critical thinking ability of fourth-grade students in the Pancasila Education subject at Elementary School Cluster VI, Sukasada District. This study was conducted to determine whether there was an effect of using the Course Review Horay model through the Wordwall Platform on improving students' critical thinking abilities. In this study, the method applied was a quasi-experimental with a quantitative approach. The population of this study included 174 fourth-grade students, with samples taken by random sampling, resulting in 26 students from SDN 4 Panji Anom as the experimental group and 32 students from SDN 1 Panji Anom as the control group. Data were collected through technical tests and documentation, then analyzed using descriptive analysis, N-Gain Score test, normality test, homogeneity test, and independent t-test. The findings of this study indicate a significant increase in students' critical thinking. Before being given treatment, the average score of students' critical thinking abilities was 47.15 and increased to 85 after being given treatment. This finding is also supported by the results of the independent t-test on the N-Gain score, which shows that t count > t table, namely 20,860 > 2,003, and a significance value of 0.000, less than 0.05. Therefore, there is a significant difference between the treatment group and the control group. From these results, it can be concluded that the implementation of the Course Review Horay model assisted by the Wordwall Platform has a significant positive impact on improving the critical thinking of Pancasila Education students. Therefore, this model is worthy of being recommended for use in grade IV as an alternative effective learning strategy.